Thursday
March 30, 2017

Post a New Question

Posted by on .

Solve by the elimination method:
7r-9s=-35
9r+7s=85

  • Algebra - ,

    (7r-9s)7=(-35) 7
    (9r+7s)9=85.9
    7(7r-9s)=765
    7(7r-9s)=-35.7
    9(9r+9s)=765
    7(7r-9s)=-245
    9.9r+9.7s=765
    7.7r-7.9s=-245
    81r+63s=765
    49r-63s=-245
    81r+63s=765
    49r-63s=-245
    (81r+63s)+(49r-63s)=765.245
    49r-63s=-245
    1230r=520
    49r-63s=-245
    130r/130=520/130
    49r-63s=-245
    r=2^3-1
    49r-63s=-245
    r=4
    49.4-63s=-245
    196-63s=-441
    63s/63=441/63
    s=7^2-1
    s=7

  • Algebra - ,

    No, no, no, no, no, no, no...I have no idea what all that nonsense above is.
    7r-9s=-35
    9r+7s=85
    Multiply the first equation by 7 and the bottom by 9 so that the s's cancel.
    49r-63s=-245
    81r+63s= 765
    130r=520
    r=4
    Now put r=4 back into any original equation.
    9(4)+7s=85
    36+7s=85
    7s=49
    s=7
    (4,7)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question